The making of the First World War - Beckett, Ian F. W. (Ian Frederick William), 1950- (Yale University Press, 2012)
Nearly a century has passed since the assassination of Austria-Hungary's Archduke Ferdinand, yet the repercussions of the devastating global conflict that followed echo still. In this book, the author turns the spotlight on twelve particular events of the First World War that continue to shape the world today. Focusing on episodes both well known and scarcely remembered, the author tells the story of the Great War from a new perspective, stressing accident as much as strategy, the small as well as the great, the social as well as the military, and the long term as much as the short term. This book is global in scope. The book travels from the deliberately flooded fields of Belgium to the picture palaces of Britain's cinema, from the idealism of Wilson's Washington to the catastrophic German Lys offensive of 1918. While war is itself an agent of change, the book shows, the most significant developments occur not only on the battlefields or in the corridors of power, but also in hearts and minds. Nor may the decisive turning points during years of conflict be those that were thought to be so at the time. With its wide reach and unexpected conclusions, this book aims at revising - and expanding - our understanding of the legacy of the First World War.